Trends in prescribing and persistence with antihypertensive therapy: results of the study PAPEETE (Population-based Analysis of Persistence and Economics of treatment with telmisartan) study - Costa, Francesco Vittorio (Farmeconomia. Health economics and therapeutic pathways, 2009)
This paper summarizes the results of the PAPEETE study (Population-based Analysis of PErsistence with treatment and Economics of TElmisartan) that assessed trends in prescriptions, determinants and timing of treatment discontinuation and/or changes in antihypertensive drug therapy in a cohort of hypertensive patients living in Pavia. In the study were included all new users 18 years old or over receiving a first prescription for diuretics, beta-blockers, calcium channel-blockers, ACE inhibitors (ACEi) or angiotensin receptor blockers (ARBs) between 1 January 2003 and 31 December 2006. The follow-up period for each patient was 12 months starting from enrolment date. Based in the presence of continuous therapy, patients were defined as persistent and non-persistent users. A total of 61,493 patients was included in the study of whom 11.2% were persistent. Persistence with the treatment seems to be associated with patient-related factors and with the class of anti-hypertensive drug initially prescribed with the lowest persistence to antihypertensive treatment with diuretics (3.0%) and the highest with ARBs (18.8%).